Government Policy for Migrant Female Workers on the Border of Sambas Regency, West Kalimantan - Majolica Ocarina Fae (Fakultas Hukum Dehasen, 2023)
The recent case study of Indonesian migrant workers has made exceptions for various parties. Their less fortunate fate is caused by the low quality of education and skills they possess so that in the end they are only forced to work in the informal sectors such as domestic workers and unskilled laborers. In the West Kalimantan border area, labor problems are becoming increasingly complex. Indeed, these workers channel economic value back to the villages, as well as bringing social change to the families left behind, especially for workers who are successful in their work. However, this has an impact on Indonesian migrant workers who cannot get legal protection from the Indonesian state and do not get employment insurance because they are not recorded in the official data of the national agency for the placement and protection of TKI (BP2TKI). To overcome the problems that occur among migrant workers in Sambas district, Several steps need to be taken, such as providing training to prospective migrant workers who will work abroad, giving the most severe punishment to individuals who provide services for placing Indonesian migrant workers abroad illegally, and strengthening agencies related to Indonesian migrant workers in carry out its duties and functions to protect Indonesian migrant workers who work abroad. For other workers, who are not as fortunate, it seems that the picture of smooth working abroad does not match the hopes and lures promised by employment agents. This research was conducted using normative quantitative method.